2009
DOI: 10.1373/clinchem.2008.116939
|View full text |Cite
|
Sign up to set email alerts
|

Salivary Leptin as a Candidate Diagnostic Marker in Salivary Gland Tumors

Abstract: Background: Since the discovery of autonomous leptin production in salivary glands, very few studies have reported on the physiological or pathological meaning of this particular cytokine in saliva. The aim of this study was to investigate the expression of leptin and its receptors Ob-Ra and Ob-Rb in parotid salivary gland tumors, with particular regard to a potential use of leptin as a tumor marker. Methods: Parotid tissue samples from healthy individuals (n = 31) and tumor patients (n = 97, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
29
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 32 publications
(32 reference statements)
5
29
1
Order By: Relevance
“…In addition, it has been reported that, under insulin resistance state, the increase of basement membrane permeability allows an enlarged passage of serum molecules [10]. Furthermore, the increase of salivary adiponectin expression could represent a biologic mechanism to counteract the sustained local inflammatory/infective state typical of obesity [9,24,25]. In fact, it is widely known that obese patients undergo frequent oral infection [24].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, it has been reported that, under insulin resistance state, the increase of basement membrane permeability allows an enlarged passage of serum molecules [10]. Furthermore, the increase of salivary adiponectin expression could represent a biologic mechanism to counteract the sustained local inflammatory/infective state typical of obesity [9,24,25]. In fact, it is widely known that obese patients undergo frequent oral infection [24].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the increase of salivary adiponectin expression could represent a biologic mechanism to counteract the sustained local inflammatory/infective state typical of obesity [9,24,25]. In fact, it is widely known that obese patients undergo frequent oral infection [24]. On the other hand, to date there are no data about the expression of the T-cadherin receptor, the suggested depot of adiponectin in salivary cells as well as in physiopathological metabolic conditions; in this scenario, we cannot exclude that an altered expression of T-cadherin could be involved in the regulation of adiponectin levels in saliva of obese patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chen et al [22] described elevated salivary levels of CA 125 in patients with ovarian cancer. Schapher et al [23] also suggested that salivary leptin was expressed in much higher amount in salivary gland tumors than in healthy parotid tissue. It has been reported that gastric cancer can also be identified at an early stage by using saliva proteome analysis [24].…”
Section: Role Of Salivary Biomarkers In Cancermentioning
confidence: 99%
“…Leptin acts as a growth factor for gastric and colorectal carcinomas as well as chondrosarcomas, and enhances the metastasis of these cancers 11–14. Recently, increased tissue leptin messenger RNA (mRNA) and leptin concentrations in breast and salivary gland tumours were reported 15 16. Indeed, salivary leptin was suggested as a diagnostic marker in salivary gland tumours 15.…”
Section: Introductionmentioning
confidence: 99%